Inflammatory score as a predictor of survival and nutritional deterioration in cancer patients: insights from a multicenter cohort study - Xie, Hailun; Wang, Shuyao; Wei, Lishuang; Lin, Siyu; Shi, Hanping; Chen, Junqiang (Frontiers in Nutrition, 2025)
Background and aimsChronic inflammation is a hallmark of cancer progression. This multicenter cohort study aimed to evaluate the prognostic value of a novel inflammatory score, derived from baseline white blood cell (WBC) count and C-reactive protein (CRP) z-scores, in predicting survival outcomes and nutritional deterioration among cancer patients.MethodsWe analyzed data from 6,568 cancer patients across multiple institutions. The inflammatory score was categorized as mild, moderate, or severe. Kaplan–Meier survival analysis, Cox proportional hazards models, and restricted cubic splines were used to assess associations with all-cause mortality. Subgroup analyses were stratified by tumor type and pathological stage. Logistic regression models quantified associations between inflammatory scores and nutritional deterioration.ResultsDose–response analyses revealed a nonlinear relationship between continuous inflammatory scores and mortality (HR = 1.200, 95% CI: 1.163–1.238, p < 0.001). Higher inflammatory scores were significantly associated with reduced survival (67.5% vs. 65.3% vs. 57.0% vs. 45.2%, p < 0.001). In fully adjusted models, severe inflammation conferred a 60.4% increased mortality risk (HR = 1.604, 95% CI: 1.464–1.757, p < 0.001) compared to mild inflammation. Subgroup analyses confirmed consistent associations across tumor types and pathological stages. Advanced-stage (III/IV) patients exhibited heightened sensitivity to inflammatory burden, underscoring its role in late-stage prognosis. Severe inflammation was also linked to higher rates of severe malnutrition (OR = 2.553, 95%CI: 2.226–2.927, p < 0.001) and cachexia (OR = 2.662, 95%CI: 2.323–3.049, p < 0.001). Validation cohorts reproduced these findings, underscoring the score’s robustness.ConclusionThe inflammatory score, integrating WBC and CRP, is a strong independent predictor of survival and nutritional deterioration in cancer patients. Its clinical utility for risk stratification and guiding targeted anti-inflammatory therapies warrants further exploration.